The alkaline hydrolysis degradation of a water-borne styrene acrylic coating - Vuong, Nguyen Thien; Hiep, Nguyen Anh (Vietnam Journal of Chemistry, 2016)
The degradation of water-borne styrene acrylic coating during the immersion in the 20 % NaOH and saturated Ca(OH)2 solutions was quantitatively investigated by using a IR spectroscopy and by measuring the sample weight and adhesion losses. The obtained results showed that during the immersion, the functional groups of coating were changed. The alkane C-H, ester C=O, C-O- and C6H5 groups decreased. Of which, the C-O- stretching shows the largest decreased. The hydroxyl group (-OH) and carboxyl group (C=O) (in -COO-) increased. The functional groups of the coating immersed in the 20 % NaOH solution changed more strongly than those of coating immersed in the saturated Ca(OH)2 solution. The formation of alkaline hydrolysis products (the OH and -COO- groups) in the coating immersed in the former was larger than in the coating immersed in the latter one. The alkane C-H, ester C=O, C-O- and C6H5 groups of the coating immersed in the saturated Ca(OH)2 solution significantly decreased while the formation of the OH and -COO- groups only slightly increased. These chemical changes caused the weight and adhesion losses of the coating. This information was useful to better understand about the major mechanisms that control of the alkaline hydrolysis degradation of water- borne styrene acrylic coating. Keywords. Alkaline hydrolysis degradation, water-borne styrene acrylic coating, IR analysis, weight loss, adhesion.